Inisiasi Bank Pakan melalui Pelatihan Budidaya Hijauan Alternatif dan Pembuatan Silase Bagi Kelompok Ternak Raung Mandiri di Desa Jambearum - Sari, Vega Kartika; Widianingrum, Desy Cahya; Yulianto, Roni; Steven, Syahrul; Basuki, Basuki; Suryono, M. Iqbal Krisna Hadi; Andreano, Rio Tito (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Sumberjambe District is one of the livestock centers in Jember Regency. The Raung Mandiri Livestock Group in Jambearum Village, Sumberjambe District, which was inaugurated at the end of 2023, already has 300 sheep. The problem faced is that members of the livestock group do not know alternative types of forage, how to propagate it and how to make silage. So far, food has been provided by searching for grass in the forest or in the fields every day, so it is hampered during the rainy season. The aim of this activity is to introduce alternative types of forage, cultivation methods and silage making in the context of initiating the Feed Bank. The methods used in carrying out activities include socialization and training, which involve participants taking an active role in activities that directly go into practice. The results of the activity showed that participants gain knowledge regarding alternative types of forage other than babandotan, elephant grass. Participants are able to reproduce, sow and plant forage seeds. Support for inputs for the initiation of the Feed Bank has been handed over in the form of chooper machines and forage seeds.